Traumatic Stress-Induced Vulnerability to Addiction: Critical Role of the Dynorphin/Kappa Opioid Receptor System - Leconte, Claire; Mongeau, Raymond; Noble, Florence (Frontiers in Pharmacology, 2022)
Substance use disorders (SUD) may emerge from an individual’s attempt to limit negative aﬀective states and symptoms linked to stress. Indeed, SUD is highly comorbid with chronic stress, traumatic stress, or post-traumatic stress disorder (PTSD), and treatments approved for each pathology individually often failed to have a therapeutic efficiency in such comorbid patients. The kappa-opioid receptor (KOR) and its endogenous ligand dynorphin (DYN), seem to play a key role in the occurrence of this comorbidity. The DYN/KOR function is increased either in traumatic stress or during drug use, dependence acquisition and DYN is released during stress. The behavioural effects of stress related to the DYN/KOR system include anxiety, dissociative and depressive symptoms, as well as increased conditioned fear response. Furthermore, the DYN/KOR system is implicated in negative reinforcement after the euphoric effects of a drug of abuse ends. During chronic drug consumption DYN/KOR functions increase and facilitate tolerance and dependence. The drug-seeking behaviour induced by KOR activation can be retrieved either during the development of an addictive behaviour, or during relapse after withdrawal. DYN is known to be one of the most powerful negative modulators of dopamine signalling, notably in brain structures implicated in both reward and fear circuitries. KOR are also acting as inhibitory heteroreceptors on serotonin neurons. Moreover, the DYN/KOR system cross-regulate with corticotropin-releasing factor in the brain. The sexual dimorphism of the DYN/KOR system could be the cause of the gender differences observed in patients with SUD or/and traumatic stress-related pathologies. This review underlies experimental and clinical results emphasizing the DYN/KOR system as common mechanisms shared by SUD or/and traumatic stress-related pathologies, and suggests KOR antagonist as a new pharmacological strategy to treat this comorbidity.